Computational modelling of the selective laser sintering process - Castro, João da Costa Teixeira (2023)
Additive Manufacturing (AM) has increased in popularity in numerous important and demanding industries due to the capability of manufacturing parts with complex geometries and reduced wastage. As one of its most popular techniques, selective laser sintering (SLS) is sought after by several industries that aim to replace conventional and more expensive processes. However, the SLS process is intrinsically complex due to the various underlying multi-physics phenomena and more studies are needed to obtain more insights about it. This has resulted in many academical interests to optimize the process and allow it to achieve industrial standards. Most of these optimization attempts are performed through experimental methods that are time-consuming, expensive and do not always provide the optimal configurations. This has led researchers to resort to computational modelling, aiming at better understanding the process to anticipate and fix the defects. The main objective of the present work was to develop a computational model capable of simulating the SLS process for polymeric applications, within an open-source framework, at particle length scale. Since distinct approaches are required for accurately simulating each step of the SLS process, different numerical methods were employed to develop a tool capable of studying the impact, in a representative section of the powder bed, of the physical parameters that can be adjusted in the process. The developed work comprises several steps, starting with an extensive study of the theoretical aspects of the SLS process, which aimed at the acquaintance with the underlying phenomena, process unwind, its parameters and their influence, as well as evaluating the existing limitations and challenges. This step was then followed by a detailed analysis of the most common employed models to represent the major phenomena and of the accuracy level of the approaches, based on the employed simplifications. A set of computational tools was then assessed and their built-in models were selected, when possible, according to the precedent literature review. Lastly, various tests were carried to obtain an experimental qualitative validation of the used code, to assure that the undetaken approach was adequate to simulate the process. The achieved developments represent a significant advance towards the detailed SLS process simulation. With the use of open-source software (LIGGGHTS e OpenFOAM), several studies were performed on a realistic powder bed section and, despite the absence of enough and more detailed experimental data, the simulation results are in agreement with the ones used for comparison. Overall, the accomplished work allowed to conclude that the employed tools constitute a great potential to study, in detail, the SLS process and its parameters influence and, therefore, contribute to its optimization.